Enolase inhibitors as therapeutic leads for Naegleria fowleri infection. - Jillian E Milanes; Victoria C Yan; Cong-Dat Pham; Florian Muller; Samuel Kwain; Kerrick C Rees; Brian N Dominy; Daniel C Whitehead; Steven W Millward; Madison Bolejack; Roger Shek; Logan Tillery; et al. (PLoS Pathogens)
Infections with the pathogenic free-living amoebae Naegleria fowleri can lead to life-threatening illnesses including catastrophic primary amoebic meningoencephalitis (PAM). Efficacious treatment options for these infections are lacking and the mortality rate remains >95% in the US. Glycolysis is very important for the infectious trophozoite lifecycle stage and inhibitors of glucose metabolism have been found to be toxic to the pathogen. Recently, human enolase 2 (ENO2) phosphonate inhibitors have been developed as lead agents to treat glioblastoma multiforme (GBM). These compounds, which cure GBM in a rodent model, are well-tolerated in mammals because enolase 1 (ENO1) is the predominant isoform used systemically. Here, we describe findings that demonstrate these agents are potent inhibitors of N. fowleri ENO (NfENO) and are lethal to amoebae. In particular, (1-hydroxy-2-oxopiperidin-3-yl) phosphonic acid (HEX) was a potent enzyme inhibitor (IC50 = 0.14 ± 0.04 μM) that was toxic to trophozoites (EC50 = 0.21 ± 0.02 μM) while the reported CC50 was >300 μM. Molecular docking simulation revealed that HEX binds strongly to the active site of NfENO with a binding affinity of -8.6 kcal/mol. Metabolomic studies of parasites treated with HEX revealed a 4.5 to 78-fold accumulation of glycolytic intermediates upstream of NfENO. Last, nasal instillation of HEX increased longevity of amoebae-infected rodents. Two days after infection, animals were treated for 10 days with 3 mg/kg HEX, followed by one week of observation. At the end of the one-week observation, eight of 12 HEX-treated animals remained alive (resulting in an indeterminable median survival time) while one of 12 vehicle-treated rodents remained, yielding a median survival time of 10.9 days. However, intranasal HEX delivery was not curative as brains of six of the eight survivors were positive for amoebae. These findings suggest that HEX requires further evaluation to develop as a lead for treatment of PAM.